THE EFFECTIVENESS OF USING WORD WALL-BASED LEARNING MEDIA IN INCREASING STUDENTS’ LEARNING ACTIVITIES ON ECONOMY LEARNING SUBJECTS AT SMA PGRI PEKANBARU - Vanessa Marensi; Suarman Suarman; Almasdi Syahza (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper analyzes students’ learning activities using word wall-based learning media. The research was conducted at SMA PGRI Pekanbaru in class X of Social Science. The research used an experimental approach with the One Group Pretest Posttest Design model. Data collection techniques used questionnaires and observation sheets. Students’ learning activity data were obtained through questionnaires. Meanwhile, based on the use of word wall learning media, data were obtained through observation. Data analysis techniques used t-test and Normality Gain (N-gain). The results indicate that the use of word wall learning media was effective in increasing students’ learning activities. It can be seen from the improvement of students’ learning activities from medium to high. Thus, it is expected for teachers, in order to achieve better results in students’ learning activities, this learning media can be used, especially in Economy learning subjects in Senior High School. In addition, further researchers can conduct the same study based on different learning subjects. Because, in addition to increasing students’ learning activities, word wall learning media can improve students’ learning outcomes and motivation.